A 3-Decade Analysis of Pancreatic Adenocarcinoma After Solid Organ Transplant. Issue 1 (January 2021) - Corral, Juan E.; Croome, Kristopher P.; Keaveny, Andrew P.; Brahmbhatt, Bhaumik; Kröner, Paul T.; Wijarnpreecha, Karn; Goswami, Rohan M.; Raimondo, Massimo; Wallace, Michael B.; Bi, Yan; Mousa, Omar Y.
Abstract : Objective: Solid organ transplant (SOT) recipients have moderately increased risk of pancreatic adenocarcinoma (PAC). We evaluated the incidence and survival of PAC in 2 cohorts and aimed to identify potential risk factors. Methods: This study performed a retrospective cohort analysis. Cohort A was extracted from the United Network of Organ Sharing data set and cohort B from SOT recipients evaluated at 3 Mayo Clinic transplant centers. The primary outcome was age-adjusted annual incidence of PAC. Descriptive statistics, hazard ratios, and survival rates were compared. Results: Cohort A and cohort B included 617, 042 and 29, 472 SOT recipients, respectively. In cohort A, the annual incidence rate was 12.78 per 100, 000 in kidney-pancreas, 13.34 in liver, and 21.87 in heart-lung transplant recipients. Receiving heart-lung transplant, 50 years or older, and history of cancer (in either recipient or donor) were independent factors associated with PAC. Fifty-two patients developed PAC in cohort B. Despite earlier diagnosis (21.15% with stage I–II), survival rates were similar to those reported for sporadic (non-SOT) patients. Conclusions: We report demographic and clinical risk factors for PAC after SOT, many of which were present before transplant and are common to sporadic pancreatic cancer. Despite the diagnosis at earlier stages, PAC in SOT portends a very poor survival. Abstract : Supplemental digital content is available in the text.